A new model for recognition, referral, and follow‐up of autism spectrum disorder: A nationwide program. Issue 10 (16th September 2022) - Dursun, Onur Burak; Turan, Bahadır; Öğütlü, Hakan; Binici, Nagihan Cevher; Örengül, Abdurrahman Cahid; Alataş, Esra; Özdemir, Rabia Madan; Taşlıbeyaz, Elif; Karaman, Selçuk; Mukaddes, Nahit Motavallı; ,
Abstract: Early diagnosis of autism certainly stands as one of the most important determinants to ensure a better prognosis of the disorder, it is common that the screening programs to ensure this, end up not being implemented in health systems of many countries. This may stem from the disadvantages of classically suggested scale‐based screening (SBS) programs. This study presents a nationwide recognition and referral model for early diagnosis of autism spectrum disorders (ASD), in order to meet the obvious need for new methods. The model consists of interactive video‐based training (IVBAT) of health care workers (HCW), a system where family physicians (FPs) record five probable indicators of autism in their family medicine information system; and is therefore, a practical referral system in which the FP may refer a child with any suggestive finding to a child psychiatrist and may well continue to monitor recently diagnosed cases. The autism teams consist of trained child psychiatrists and coordinators, who delivered trainings to 29, 612 FPs and 23, 511 nurses countrywide. Of 98.8% FPs were trained throughout the country. Total of 1, 863, 096 children were reported to have a brief examination of autism signs in Family Medicine Units by trained FPs and nurses. A total of 55, 314 (2.96%) these children were deemed at risk for ASD and were referred to child psychiatrists. In the evaluation of 55, 314 children by child psychiatrists, 10, 087 cases were diagnosed with developmental disorders, while 3226 of children at risk were diagnosed with autism. The results of this study, which reached to the largest sample to date, suggest that some other alternative methods, in addition to SBS should also be tested in order to screen ASD. Lay Summary: In this study, a nationwide recognition and referral model for early identification of autism spectrum disorders (ASD) is presented. Scale‐based screening (SBS) is the most recommended model for autism, however, it is clear that most countries can not implement this model in their health system. The results of this study, which reached to the largest sample to date, suggest that SBS may not be the only me for screening ASD and that alternative methods should be tried, as there is an obvious need for exploratory approaches.